Analysis of Human Resource Performance Using the Human Resources Scorecard Method in The Production Department at PT. X (Jurnal Sistem Teknik Industri, 2024)
PT X is a manufacturing company engaged in the sector of herbal medicines, cosmetics, household supplies, and medical equipment. At PT X there are several problems that can lead to a decrease in the performance of human resources in the company's production department, including the production of capsule drugs that do not reach their targets, a lack of employee motivation at work, and a lack of employee discipline. Based on these issues, PT X is required to implement a performance measurement based on the Human Resources Scorecard (HRSC) method and the Analytic Network Process (ANP) method in order to weight its performance indicators. The objective of this study is to measure the human resource performance of the production department of PT X and determine the performance indicators that require the most improvement. The results of measuring human resource performance using the Human Resource Scorecard indicate that the value of human resource performance in employees of PT X is 2,555613 and it can be concluded that the HR performance is in the not good category because the HR performance value of production department of PT X is in the range of 1,8 - 2,6. The perspective that must be prioritized by PT X in improving its HR performance is the financial perspective because it has the lowest perspective value, precisely on the objective strategy of increasing employee effectiveness because it has the greatest priority weight and the KPI achievement score is very low, which is 1.